Rent-sharing under different bargaining regimes: Evidence from linked employer-employee data - Michael Rusinek; François Rycx (National Bank of Belgium, 2008)
In many European countries, the majority of workers have their wage rates determined directly by industry-level agreements. For some workers, industry agreements are supplemented by firm-specific agreements. Yet, the relative importance of individual company and industry agreements (in other words, the degree of centralisation) differs drastically across industries. The authors of this paper use unique linked employer-employee data from a 2003 survey in Belgium to examine how these bargaining features affect the extent of rent-sharing. Their results show that there is substantially more rent-sharing in decentralised than in centralised industries, even when controlling for the endogeneity of profits, for heterogeneity among workers and firms and for differences in characteristics between bargaining regimes. Moreover, in centralised industries, rent-sharing is found only for workers that are covered by a company agreement. The findings of this paper finally suggest that, within decentralised industries, both firm-specific and industry-wide bargaining generate rent-sharing to the same extent.
Keywords: J31; J51; 330; Rent-sharing; collective bargaining; propensity score matching.; Tarifverhandlungen; Tarifverhandlungen; Betriebsvereinbarung; Vergleich; Lohnbildung; Rententheorie; Belgien